Letter (copy) : International Peace Campaign - Tewson, Vincent
012b-0064-001 Secretary's. HVT/FC/245. JRS/DS. 25th January, 1939. Mr. J. R. Shanley, The Amalgamated Union of Upholsterers, Swinton House, 324, Gray's Inn Road, W.C.1. Dear Mr. Shanley, INTERNATIONAL PEACE CAMPAIGN. I have your letter of the 21st instant on the above subject. I may say that the full circumstances have been reported to the General Council who have completely endorsed the action taken. Yours sincerely, Assistent Secretary. 292/946/12b/64